Attribution of climate change and climate change impacts: Part of the Advanced AGNES Courses on Climate Outlook, Impact Assessment, and Climate Risk Assessment - Engdaw, Mastawesha Misganaw; Ghosh, Aniruddha (2025)
Attribution science of climate change — encompassing both slow- and sudden-onset changes in the climate system and the attribution of their consequent impacts — provides the most robust evidence of human influence on the climate system. However, expertise in attribution science, which is essential for generating evidence on the respective roles of industrialized and developing regions in driving climate change, remains limited. African countries are among the most affected by this cause-and-effect relationship. Consequently, climate negotiations at the COPs often center on discussions between industrialized nations, as major emitters, and developing countries, as the primary victims of climate change impacts. Therefore, a critical understanding of scientific methods that link greenhouse gas emissions to changes in climate extremes and their associated impacts is vital for African climate negotiators. As part of ongoing efforts to strengthen this capacity, the African Group of Negotiators Expert Support (AGNES) has been actively working to build the technical competence of African negotiators. This report documents the capacity-building trainings conducted on the “Attribution of Climate Change and Its Impacts” for African climate negotiators.